Material requirement planning for build-to-sequence supply: a multi-level optimisation approach - Bányai, Ágota (Journal of Production Engineering, 2023)
Material requirement planning (MRP) plays an important role in the life of production companies, because it has a great impact on the efficiency of manufacturing operations and it influences the total cost. Just-intimeand just-in-sequence supply offer new solutions to improve the cost-efficiency from inventory holding point of view. Within the frame of this article the author focuses on the build-to-sequence strategy of just-in-sequence supply and demonstrate an integrated approach of material requirement planning. The suggested methodology includes the determination of build-to-sequence orders, the optimisation of material requirement from lead time and cost point of view and determine the optimal sequence of operations to fulfil build-to-sequence demands. The computational results show, that the integrated optimisation leads to an increased cost efficiency, while the required manufacturing operations are performed with a decreased lead time.